The Effect of Disease and Season to Hepatopancreas and Intestinal Mycobiota of Litopenaeus vannamei - Li, Juan; Jiang, Haiying; Li, Linmiao; Zhang, Xiujuan; Chen, Jinping (Frontiers in Microbiology, 2019)
Increasing evidence has manifested that the gut bacterial microbiota of shrimps is closely related to the environmental factors, host developmental stage and health status like that of humans and animals does. These studies have provided an important guidance for improving shrimp culture benefits. In practice, aside from bacteria, eukaryotic microorganisms dominated by fungal microbiota (mycobiota), also play a key role in host growth, metabolism and homeostasis. However, little so far is known about the mycobiota in the digestive tract of shrimp. In this study, we used high-throughput sequencing of internal transcribed spacer 1 region to characterize the hepatopancreas and intestinal mycobiota of Pacific white shrimp and their connections with disease incidence and seasonal variation. The results showed that the hepatopancreas and intestinal mycobiota of Litopenaeus vannamei are dominated by the phyla Ascomycota and Basidiomycota, and the genera Alternaria, Tuber, Hortaea, Sarocladium and Stagonospora. The fungal microbiota significantly varies under the influence of disease and seasonal variation. Sick shrimps had a higher level of potential pathogenic fungus, Candida in the intestine. Healthy shrimps had a higher abundance of the genera Didymella and Filobasidium in the gut, and Pyrenochaetopsis in the hepatopancreas. Of note, most of the fungi carried by Pacific white shrimps were pathogens to humans. This study has revealed the intestinal and hepatopancreas mycobiota of L. vannamei and the effects of diseases and seasonal variation to the mycobiota. Our study provides important guidance for Pacific white shrimp farming and sheds further insight on the fungal microbiota.